2017
DOI: 10.1186/s12903-017-0361-x
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of Helicobacter pylori in the dental biofilm and saliva samples of children with dyspeptic complaints

Abstract: BackgroundThe oral cavity can be an extra-gastric reservoir for Helicobacter pylori (H.pylori). This can play a role in the pathogenesis of halitosis, glossitis, recurrent aphthous stomatitis, and dental caries. The present study was conducted to detect the presence of H.pylori within the dental biofilm and in saliva samples collected from children suffering from dyspepsia and children without any gastrointestinal complaints. Associations with gastric infection, halitosis, and some oral parameters were also ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 61 publications
(102 reference statements)
0
31
0
Order By: Relevance
“…The authors observed that H. pylori can occur in the oral cavity aside and independently of the stomach. They also found an association between the presence of H. pylori and halitosis …”
Section: Invasive Testsmentioning
confidence: 89%
“…The authors observed that H. pylori can occur in the oral cavity aside and independently of the stomach. They also found an association between the presence of H. pylori and halitosis …”
Section: Invasive Testsmentioning
confidence: 89%
“…[ 39 ] observed that after eradication of H. pylori with 3 antibiotic treatment, most of the patients had decreased halitosis in long-term follow-ups. In another study [ 40 ], organoleptic scoring and the BANA test were both used to evaluate halitosis among gastric H. pylori positive and negative children. According to organoleptic scoring and BANA test, there was no clear relationship found between the gastric presence of H. pylori and halitosis.…”
Section: Literature Review/ Discussionmentioning
confidence: 99%
“…Some epidemiological studies have revealed that patients with dental caries or poor oral hygiene were more likely to harbour H. pylori in oral cavity or gastric tissue 13 , 14 . These findings suggest that the presence of cariogenic bacteria is involved in infection of the oral cavity with H. pylori .…”
Section: Introductionmentioning
confidence: 99%